Extraction of natural food color from Celosia cristata using orbital shaking apparatus - Anjum, Nadira; Masih, Dorcus; Sheikh, Mohd Aaqib; Rahman, Rukhsana (Journal of Postharvest Technology, 2021)
As there is a growing demand for eco-friendly and non-toxic food colorants, the colors obtained from plant sources have proven to be an alternative to the synthetic food colors. In the present study, natural pigment and color was extracted from the flowers of Celosia cristata using orbital shaking apparatus. Three different temperatures (20, 40, and 60 oC) and three different solvents (distilled water, 30% ethanol, 50% ethanol) were used for the extraction. Optimum extraction conditions for maximizing the total betalin content (17.67 mg/100g), antioxidant activity (38.54%) and colorant yield (23.98%) were temperature of 40 oC using distilled water for an extraction period of 2 hours. Betalin content decreased at higher temperature (60 oC) of extraction that depicts the thermal degradation of the betalin content. The solid liquid ratio taken for extraction was 1:10 (w/v).